An alternative downstream translation start site in the non-TIR adaptor Scimp enables selective amplification of CpG DNA responses in mouse macrophages - Curson, James Eb; Luo, Lin; Liu, Liping; Burgess, Belinda J; Bokil, Nilesh J; Wall, Adam A; Brdicka, Tomas; Kapetanovic, Ronan; Stow, Jennifer L; Sweet, Matthew J (Immunology and cell biology, 2022)
Toll-like receptor (TLR) signaling relies on Toll/interleukin-1 receptor homology (TIR) domain-containing adaptor proteins that recruit downstream signaling molecules to generate tailored immune responses. In addition, the palmitoylated transmembrane adaptor protein family member Scimp acts as a non-TIR-containing adaptor protein in macrophages, scaffolding the Src family kinase Lyn to enable TLR phosphorylation and proinflammatory signaling responses. Here we report the existence of a smaller, naturally occurring translational variant of Scimp (Scimp TV1), which is generated through leaky scanning and translation at a downstream methionine. Scimp TV1 also scaffolds Lyn, but in contrast to full-length Scimp, it is basally rather than lipopolysaccharide (LPS)-inducibly phosphorylated. Macrophages from mice that selectively express Scimp TV1, but not full-length Scimp, have impaired sustained LPS-inducible cytokine responses. Furthermore, in granulocyte macrophage colony-stimulating factor-derived myeloid cells that express high levels of Scimp, selective overexpression of Scimp TV1 enhances CpG DNA-inducible cytokine production. Unlike full-length Scimp that localizes to the cell surface and filopodia, Scimp TV1 accumulates in intracellular compartments, particularly the Golgi. Moreover, this variant of Scimp is not inducibly phosphorylated in response to CpG DNA, suggesting that it may act via an indirect mechanism to enhance TLR9 responses. Our findings thus reveal the use of alternative translation start sites as a previously unrecognized mechanism for diversifying TLR responses in the innate immune system.
Keywords: DNA; makrofágy; signální transdukce; myši; Mice; Adaptor protein; src-Family Kinases; Animals; Signal Transduction; alternative translation start site; macrophage; protein translation; Macrophages; toll-like receptory; zvířata; Toll-like receptor; Toll-Like Receptors; CpG DNA; skupina kinas odvozených od src-genu